2021
DOI: 10.18502/htaa.v4i4.6864
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Spiritual Health and Stress, Depression, and Anxiety in Hemodialysis Patients

Abstract: Background: Chronic diseases confront the patient with questions about the meaning and the purpose of life, and many patients recognize spiritual health as a factor in creating meaning and purpose in life and improving the quality of life. Objectives: The aim of this study was to determine the relationship between spiritual health and stress, depression, and anxiety in hemodialysis patients of Birjand Special Diseases Center in 2019. Methods: In this descriptive-analytical cross-sectional study, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Depression is one of the psychological disorders that impairs the functionality of individuals. [21] Most of the patients participating in our study do not have social support. It has been found that the social supports given are mostly in the form of meeting physical needs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Depression is one of the psychological disorders that impairs the functionality of individuals. [21] Most of the patients participating in our study do not have social support. It has been found that the social supports given are mostly in the form of meeting physical needs.…”
Section: Discussionmentioning
confidence: 96%
“…It was found that patients with high mental well-being showed lower depressive symptoms; our results are in agreement with the sources. [21,35] The psychiatric disorder that causes the most hopelessness is known as depression. Although hope has no healing power, it encourages the patient to continue the fight and seek clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation